Obstetric and neonatal outcomes for women intending to use immersion in water for labour and birth in Western Australia (2015–2016): A retrospective audit of clinical outcomes - Lewis, Lucy; Hauck, Yvonne; Butt, Janice; Hornbuckle, J. (Blackwell Publishing, 2018)
Background: Research supports water immersion for labour if women are healthy, with no obstetric or medical risk factors. Aims: To evaluate the obstetric and neonatal outcomes of women intending to use immersion in water for labour or birth. Methods: Retrospective audit of clinical outcomes for women intending to labour or birth in water conducted between July 2015 and June 2016, at a tertiary maternity hospital in Western Australia. Obstetric and neonatal data were collected from medical records. Multivariable logistic regression was utilised to investigate women who laboured in water stratified by those who birthed in water. Results: A total of 502 women intended to labour or birth in water; 199 (40%) did not and 303 (60%) did. The majority of women using water immersion (179 of 303; 59%) birthed in water. Multiparous women were more likely than primparous to birth in water (73% vs 46%; P < 0.001). Women who birthed in water were at increased odds of: a first stage labour =240 min (odds ratio (OR) 2.56, 95% CI 1.34–4.87, P = 0.004); a second stage =60 min (OR 3.53, 95% CI 1.82–6.84, P < 0.000); a third stage labour of 11–30 min (OR 2.15, 95% CI 1.23–3.78, P = 0.008); and having an intact perineum (OR 3.10, 95% CI 1.70–5.64, P < 0.000). Conclusion: Not all women who set out to labour and birth in water achieve their aim. There is a need for high-quality collaborative research into this option of labour and birth, so women can make an informed choice around this birth option.